ABR profile in children with congenital rubella syndrome at Hasan Sadikin General Hospital - Wijana Wijana; Alfira Ulfa (PERHATI-KL, 2019)
Background: Congenital Rubella Syndrome (CRS) refer to a condition of variable birth defects, such as hearing impairment, congenital heart defects, cataract or congenital glaucoma, and others. In Indonesia, the incidence rate of rubella infection in 2015 was 3.2 per 100.000 live birth and increasing to 5.6 per 100.000 live birth in 2017. Rubella vaccination can decrease the incidence of CRS, however it has not been implemented in many developing country. Hearing impairment is the most common clinical manifestation among CRS cases. Purpose: This study was performed to know the hearing profile on CRS from January until December 2018, at Hasan Sadikin Hospital. Methods: A retrospective descriptive study design was conducted. Data was obtained from medical records and Auditory Brainstem Response (ABR) results, between January until December 2018, at Dr. Hasan Sadikin General Hospital, Bandung. Results: There were 60 CRS patients, 53 of them (88%) had hearing loss. Profound Sensorineural Hearing Loss (SNHL) in 27 patients (45%), severe SNHL in 18 patients (30%), 3 of them were unilateral, moderate unilateral SNHL in 3 patients (5%), mild SNHL in 5 patients (8%) consisted of 2 unilateral SNHL and 3 bilateral SNHL. Normal hearing in 7 patients (12%). Conclusion: Eighty eight percent of CRS patients had hearing loss, 75% with bilateral SNHL. Follow-up and management for these patients required multidisciplinary approach such as paediatrics, ophthalmologic, physical medicine and rehabilitation, and parental support. Latar belakang: Sindrom Rubella Kongenital (SRK) mengacu pada berbagai kondisi cacat lahir, seperti gangguan pendengaran, cacat jantung kongenital, katarak atau glaukoma kongenital, dan lain-lain. Di Indonesia, tingkat kejadian infeksi rubella pada tahun 2015 adalah 3,2 per 100,000 kelahiran hidup dan meningkat menjadi 5,6 per 100,000 kelahiran hidup pada tahun 2017. Vaksinasi rubella dapat mengurangi kejadian SRK, namun belum diterapkan di banyak negara berkembang. Gangguan pendengaran adalah manifestasi klinis paling umum di antara kasus SRK. Tujuan: Penelitian ini dilakukan untuk mengetahui profil pendengaran pada SRK, dari Januari sampai dengan Desember 2018, di Rumah Sakit Hasan Sadikin. Metode: Penelitian ini adalah deskriptif retrospektif. Data diperoleh dari rekam medis dan hasil Auditory Brainstem Response (ABR) antara Januari hingga Desember 2018 di Rumah Sakit Umum Dr. Hasan Sadikin, Bandung. Hasil: Didapatkan 60 pasien SRK, 53 pasien (88%) mengalami gangguan pendengaran. Gangguan pendengaran sensorineural (GPSN) sangat berat terdapat pada 27 pasien (45%), GPSN berat pada 18 pasien (30%), 3 di antaranya adalah GPSN unilateral. GPSN unilateral sedang pada 3 pasien (5%), GPSN ringan pada 5 pasien (8%) terdiri dari 2 gangguan pendengaran unilateral dan 3 GPSN bilateral. Pendengaran normal pada 7 pasien (12%). Kesimpulan: Delapan puluh delapan persen pasien SRK mengalami gangguan pendengaran, 75% dengan GPSN bilateral. Tindak lanjut dan penatalaksanaan untuk pasien ini memerlukan pendekatan multidisiplin: spesialis THT, spesialis anak, spesialis mata, spesialis kedokteran fisik dan rehabilitasi, serta dukungan orang tua.